On the Dirac equation with PT-symmetric potentials in the presence of position-dependent mass - Castro, L. B. [UNESP] (Elsevier B.V., 2011)
The relativistic problem of fermions subject to a PT-symmetric potential in the presence of position-dependent mass is reinvestigated. The influence of the FT-symmetric potential in the continuity equation and in the orthonormalization condition are analyzed. In addition, a misconception diffused in the. literature on the interaction of neutral fermions is clarified. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Dirac equation; Non-Hermitian potentials; PT symmetry